The Effect of Nurse Hand Hygiene Education on Nosocomial Infection Prevention Knowledge in the Inpatient Room, Dahlia Room, Sayang Regional General Hospital, Cianjur - Dewi Amir, Mayasyanti; Hikmayati, Ucu; Ida, Ida (Universitas Syiah Kuala, 2024)
Prevention of HAIs can be done if health facilities consistently implement infection prevention and control programs. The purpose of the study was to determine the Effect of Nurse Hand Hygiene Education on the Knowledge of Nosocomial Infection Prevention. Knowledge is the ability of an individual to recall names, words, inspirations, formulas, and so on. Health education is a way to influence others, whether individuals, groups, or communities, so that they do what the education or health promotion actors expect. The type of research uses a quasi experiment with a prepost test design. The population in this study is 461 people and the sample itself is 18 people with the Cluster Sampling technique. The instrument used in this study is a questionnaire. Data collection technique by observation. The analysis used was univariate and bivariate using the Wilcoxon test. The results of the study showed that most of the respondents had a sufficient level of knowledge with a total of 9 respondents (50%) before being given the intervention, Most of the respondents had a good level of knowledge after being given the intervention with a total of 13 respondents (72.2%) after being given the intervention and there was an effect of hand hygiene education on the knowledge of nosocomial infection prevention with PValue = 0.000 0.05. There is a need to improve human resources, especially nurses through education or trainings to improve skills, especially in the prevention of nasocomial infections.